Pengaruh Motode Bermain Terhadap Motivasi Siswa Pada Materi Servis Atas Pembelajaran Bola Voli Sekolah Menegah Pertama - Darmawan, Tias Lucky; Nasution, Nana Suryana; Nugroho, Setio (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2021)
This study aims to examine the effect of playing methods on students' motivation on service material in junior high school volleyball learning. This study used an experimental method with the design of One Group Pretest Posttest Design. The population used was all students of class VIII totaling six classes of 215 students, taken using cluster random sampling technique into one class of 36 students. The data collection technique that is used in this research was a questionnaire through validity and reliability tests. The data analysis technique used the z test, through the prerequisite normality test with pretest and posttest data with the Sig. 0.253 and 0.261> 0.05, these results indicate that the data is normally distributed. The z test results show the value of Sig. 2 tailed 0,000. Therefore 0.000 <0.05, it can be concluded that there is an effect of the playing method on student motivation in service material for junior high school volleyball learning.Â